A modified level set algorithm based on point distance shape constraint for lesion and organ segmentation. (January 2019) - Li, Xu; Li, Chunming; Liu, Hairong; Yang, Xiaoping
Highlights: A point distance shape constraint is proposed. The constraint is linear combination of Euclidean distance of user selected points. The constraint can describe various of shapes by selecting different number of points. Various image datasets are used to show the efficiency of the proposed method. Parameter selection is carried out before segmenting each kind of images. Abstract: Purpose: The segmentation of organs and lesions from medical images is a challenging task due to the presents of noise, intensity inhomogeneity, blurry/weak boundaries. In this paper, a point distance shape constraint is proposed and incorporated in the level set framework for the segmentation of objects with various shapes. Methods: The proposed shape constraint is a linear combination of the Euclidean distance of user selected points. By selecting different numbers of points, it can generate different shape constraints and therefore is more flexible in dealing with different shapes. Then this shape constraint is incorporated into the variational level set framework. A convex relaxation is applied to get a convex model which can be efficiently solved by a primal-dual hybrid gradient algorithm. Results: The proposed algorithm is tested on 60 CT images with the nodular type of hepatic cellular cancer (HCC), 100 ultrasound kidney images, 20 prostate MR images, 20 lumbar CT images and 100 transrectal ultrasound prostate images. The algorithms performance is evaluated using a number of metrics by comparison with expert delineations. The validation results show that, for five datasets mentioned previously, the average DSCs of the proposed algorithm are 95.6% ± 1.4%, 94.3% ± 3.1%, 91.3% ± 3.8%, 92.7% ± 1.5% and 94.4% ± 2.2% respectively. Both quantitative and qualitative evaluation confirm that the proposed method can provide more accurate segmentation than four state-of-the-art methods. Conclusion: The proposed point distance shape constraint segmentation model can accurately segment organs and lesions with a number of shapes in medical images.